Study of the machinability and mechanical behavior of a bio composite material reinforced with lignocellulosic fibers - Riyadh Benyettou (University of M'Sila, 2024)
The thesis conducted a comprehensive examination of the physical properties of newly manufactured Date Palm Fiber/ Iso polyester composites (DPFPs) in three different configurations: unidirectional (UD) and cross-linked (C), with layer numbers ranging from 2 to 4. Moreover, it explored the mechanical behavior and the machinability of two recently developed biocomposites: DPFP40 (Date Palm Fiber/ Iso polyester), characterized by a 40% by-weight fiber reinforcement, and PFPEs (palm fiber powder/epoxy) featuring an 18% by-weight fiber reinforcement. The examination of drilling behavior of these bio composites yields crucial insights into specific mechanical properties. This analysis considers factors such as assessing the final surface quality of drilled holes to understand the biocomposite's reaction to cutting forces, as well as investigating the impact of various drilling parameters including spindle speed, feed rate, materials and point angles of drill bits. These investigations aid in optimizing machining conditions to enhance overall mechanical performance of developed biocomposites. The study focused on DPFPs' water absorption behavior across different water types and examined DPFP40 and PFPEs drilling behaviors under various cutting conditions. Three optimization and modeling methods, including Artificial Neural Networks (ANN), Response Surface Methodology (RSM), and the Taguchi approach, were developed for predictive capabilities. A water absorption study revealed a linear correlation between absorption rates and fiber content. DPFP40 drilling analysis indicated optimal parameters for delamination, circularity, and cylindricity errors of drilled holes. ANN and RSM models demonstrated excellent alignment with experimental data. PFPEs drilling characteristics were assessed, highlighting the impact of feed rate, spindle speed, and drill point angle on circularity and cylindricity errors of drilled holes. ANN and Taguchi models accurately predicted experimental results, providing valuable insights for improving the machinability of Natural Fiber Reinforced Composites (NFRCs) in lightweight structural applications across various industries.
أجرت هذه الأطروحة فحصًا شاملاً للخصائص الفيزيائية لمركبات ألياف نخيل التمر / ايزو بوليستير (DPFPs) المصنعة حديثًا في ثلاثة تكوينات مختلفة: أحادية الاتجاه ) UD ( ومترابطة ) C(، مع أرقام طبقات تتراوح من 2 إلى 4. علاوة على ذلك، استكشفت هذه الأطروح ة السلوك الميكانيكي و إمكانية تصنيع نوعين من المركبات الحيوية التي تم تطويرها مؤخرًا : DPFP40 )ألياف نخيل التمر/ ايزو بوليستير(، التي تتميز بتقوية الألياف بنسبة 40 % بالوزن، و PFPEs )مسحوق ألياف النخيل/الإيبوكسي( التي تتميز بتعزيز الألياف بنسبة 18 % بالوزن. يوفر فحص سلوك الثق ب لهذه المركبات الحيوية معلومات مهمة عن الخواص الميكانيكية المحددة. يأخذ هذا التحليل في الاعتبار عوامل مثل تقييم جودة السطح النهائية للثقوب لفهم استجابة المركب الحيوي لقوى القطع، بالإضافة إلى دراسة تأثير معلمات الثقب المختلفة، بما في ذلك سرعة المغزل، ومعد ل التغذية ومواد وزوايا نقطة الثق ب. تتيح هذه التحقيقات تحسين ظروف التشغيل لتحسين الأداء الميكانيكي العام للمركبات الحيوية المطورة . ركزت الدراسة على سلوك امتصاص الماء ل DPFPs عبر أنواع المياه المختلفة وفحصت سلوكيات ثق ب DPFP40 و PFPE في ظل ظروف القطع المختلف ة. تم تطوير ثلاث طرق للتحسين والنمذجة، بما في ذلك الشبكات العصبية الاصطناعية ) ANN (، ومنهجية سطح الاستجابة ) RSM (، ونهج تاجوتشي، من أجل القدرات التنبؤية. كشفت دراسة امتصاص الماء عن وجود علاقة خطية بين معدلات الامتصاص ومحتوى الألياف. أشار تحليل ثق ب DPFP40 إلى المعلمات المثالية لعامل التصفيح والأخطاء الدائرية والأسطوا ن ية لل ثقوب المحفورة. أظهرت نماذج ANN و RSM توافقًا ممتازًا مع البيانات التجريبية. تم تقييم خصائص ثق ب PFPEs ، مع تسليط الضوء على تأثير معدل التغذية، وسرعة المغزل، وزاوية نقطة الحفر على أخطاء الدائرية XIV والأسطوانية. تنبأ نموذجا ANN و Taguchi بالنتائج التجريبية بدقة، مما يوفر رؤى قيمة لتحسين إمكانية تصنيع المركبات المقواة بالألياف الطبيعية ) NFRCs ( في التطبيقات الهيكلية خفيفة الوزن عبر مختلف الصناعات .